Activating metaphors: exploring the embodied nature of metaphorical mapping in political discourse - Giovanelli, Marcello (Taylor & Francis, 2015)
Objectives: This activity allows students to explore the embodied nature of metaphor and its interpretative significance by using gesture and physical movement. Students also understand how, in metaphor, abstract entities are conceptualized in terms of something more concrete.